Entre a participação e a omissão: uma análise da efetividade do Conselho Estadual dos Direitos da Pessoa com Deficiência do Pará - BARROS JÚNIOR, Antonio Carlos Sampaio Martins de (Universidade Federal do Pará, 2018)
Amidst of contemporary democratic constructions, based on an instrumental approach, two overwhelming movements gain prominence: incoming inequality and the crisis of representativeness. It is, in a way, in opposition to such a scenario that the participatory institutions arise, like legal councils, as is the case of those related to people with disabilities. Thus, the present study aims to analyze the effectiveness of one of these experiences, the Conselho Estadual dos Direitos da Pessoa com Deficiência do Pará, through a qualitative research inspired by dialectical historical materialism, its design strongly influenced by the formulations of Silva and Lavalle. Their sources include bibliography, documents and interaction with the subjects directly involved, using participant observation, interviews and questionnaires. Some of the meanings of democracy, the political action of society and the state, issues related to participation, representation, deliberation and operationalization of activities within the councils are analyzed, as well as their interaction with the political environment, in order to understand the main constraints and incentives for its performance, whose results are far below theoretical prescriptions with normative bias, and pertinent legislation, in the face of institutional and relational limitations.